Profil Pengasuhan Orangtua Keluarga Penghafal Al-Qur’an (Studi Kasus di Keluarga X Jorong Kayu Manang) - Desi Ratna Sari; Ismaniar (Ranah Research : Journal of Multidisciplinary Research and Development, 2022)
This research is motivated by the phenomenon of the uniqueness of a family in Jorong Kayu Manang. Where in the family have children who memorize the whole Al-quran. This is of course based on parental care so that children are able to memorize the Al-quran. The focus of this research is 1) How is the time that is applied in the parenting of Al-Qur'an memorizing in X family. 2) What is the method used in parenting. 3) How is the material taught in Parenting. This type of research is a qualitative research with a case study method using data collection techniques by means of observation, interviews and documentation then analyzed using triangulation techniques. The results of this study are 1) the time that is applied in the parenting of the Al-quran memorizing family in X family is divided into three. First the morning before and after the dawn prayer, the second afternoon or evening along with the recitation schedule and finally after sunset prayer and at bedtime. 2) The method used in the parenting of the Al-quran memorizing family in the X family is no specific method. All steps or methods are adjusted according to what is contained in the context of the Al-quran. 3) The material taught in the parenting of the Al-quran memorizing family in X family also has no special material. All the material taught is in accordance with what is found in the Al-quran.